ANALISIS DETERMINAN PRODUKTIVITAS PRODUKSI KERAJINAN GERABAH DI KABUPATEN SUMBAWA - K Kamaruddin; D Devi (Pusat Riset dan Publikasi, 2023)
This study aims to determine the determinants of the productivity of pottery production in Sumbawa Regency which consist of business capital and working hours. This research is a causal associative research with quantitative techniques. This research is a population study, where in this study a total population of 30 people was used as the research sample. The method used to collect data is to use a questionnaire. All data that has been collected will be processed using the help of the SPSS program to be studied using techniques which include multiple linear regression analysis, individual parameter hypothesis testing (t test), simultaneous parameter hypothesis testing (F test), and determinant coefficient test (R2). The results of this study indicate that business capital and working hours have a positive and significant effect on the productivity of pottery production in Sumbawa Regency, both partially and simultaneously. The ability of the variables of business capital and working hours to vary the variable changes in the productivity of pottery handicraft production in Sumbawa Regency is 98.5%, while the remaining 1.5% is influenced by other variables outside this research model, such as competence, work experience and others.